The ball in the air : a golfing adventure - Bamberger, Michael, 1960- (Avid Reader Press, an imprint of Simon & Schuster, Inc., 2023)
"Here is the story of modern golf that is not on TV. This is our story, we who pay to play, who can't wait to get another crack at the game, even when golf doesn't love us back. And just as every round is an adventure, every life in golf is, too: We start at home, head on out, endure a series of events, fortunate and otherwise, and hang on for dear life as we play our way back to the house. In these pages, we celebrate the thrill of it all, as we start, turn, and finish this game of a lifetime"--Amazon.